2(x-3)+21=-03

Simple and best practice solution for 2(x-3)+21=-03 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+21=-03 equation:


Simplifying
2(x + -3) + 21 = -3

Reorder the terms:
2(-3 + x) + 21 = -3
(-3 * 2 + x * 2) + 21 = -3
(-6 + 2x) + 21 = -3

Reorder the terms:
-6 + 21 + 2x = -3

Combine like terms: -6 + 21 = 15
15 + 2x = -3

Solving
15 + 2x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 2x = -3 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = -3 + -15
2x = -3 + -15

Combine like terms: -3 + -15 = -18
2x = -18

Divide each side by '2'.
x = -9

Simplifying
x = -9

See similar equations:

| 7(x-8)-8(y+4)=80 | | -144/9 | | 30=36a+6b+c | | 27=4x+7(x-4) | | 2+-4+-5n-7+3n= | | 7x-9x+4=x-8+12 | | 2x-5(2x-10)=18 | | 8(8p+4)-8p=-27-3p | | 4g+8g+2g+9g+3g= | | 3x-5y=33-5x | | -16x-3y=12 | | 27w=-3w | | 456c=4 | | -15+5a=6a | | 10+x=5(x)+40 | | W-13.2=10.4 | | f(-6x)=6x^2-4 | | (3n+5)(n-2)-3n(n+1)=6 | | G-72=36 | | -14-63-(-52)= | | 4x-2-4= | | -6-6p+-1= | | -2(-7x+3)+3x=8x-15 | | 27th=-3w | | log^3(3x+8)=log^3(x^2+x) | | 3x-24+x=180 | | 2n^2+2n=4 | | 0.05x+0.09(10000-1x)=240 | | 4y=-1x+5 | | 87-(-34)+13= | | 3/5*5/6= | | 3(x-8)=2(3x+21) |

Equations solver categories